2010
DOI: 10.1142/s0217979210064228
|View full text |Cite
|
Sign up to set email alerts
|

Core-Tube Morphology of Multiwall Carbon Nanotubes

Abstract: The present paper investigates the cross-sectional morphology of Multiwalled Carbon Nanotubes (MWNTs) restrained radially and circumferentially by an infinite surrounding elastic medium, subjected to uniform external hydrostatic pressure. In this study, a two-dimensional plane strain model is developed, assuming no variation of load and deformation along the tube axis. We find some characteristic cross-sectional shapes from the elastic buckling analysis. The effect of the surrounded elastic medium on the cross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Moreover, much attention has been given to the structural morphology of the core/shell structure. Some authors have recently demonstrated the cross-sectional morphology of carbon nanotubes embedded in an elastic medium [15,16,17]. These results clearly show that interactions between shells and cores lead to some novel wavy-shaped buckling deformation patterns.…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, much attention has been given to the structural morphology of the core/shell structure. Some authors have recently demonstrated the cross-sectional morphology of carbon nanotubes embedded in an elastic medium [15,16,17]. These results clearly show that interactions between shells and cores lead to some novel wavy-shaped buckling deformation patterns.…”
Section: Introductionmentioning
confidence: 85%
“…Note that i j c  is symmetric. The set of Equations (15), (20), and (21) allows for the evaluation of I U .…”
Section: Inter-tube Coupling Energymentioning
confidence: 99%
“…Nevertheless, due to their nanometric scales, the similarities and differences in the buckling patterns compared with those of their macroscopic counterparts are not trivial. This complexity has motivated tremendous efforts toward the analysis of the buckling of carbon nanotubes under diverse loading conditions: axial compression [6][7][8][9][10], radial compression [11][12][13][14][15][16][17][18][19][20][21][22], bending [23][24][25][26][27][28], torsion [29][30][31][32], and combinations of these [33].…”
Section: Introductionmentioning
confidence: 99%
“…carbon nanotubes embedded in an elastic medium. [9][10][11] In most cases quantum theory is necessary for the description of the organization forms of matter. But even the interpretation of modern quantum theory seems still to be an open question, as is demonstrated in Refs.…”
Section: Introductionmentioning
confidence: 99%